Gen Z’s Oversharing on Instagram Stories - Ade Kusuma; Wildan, Wildan (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Oversharing was initially used to explain the condition where someone excessively discloses more private information about themselves to the general public, both online and offline. Oversharing on social media by adolescents is a significant problem in the digital age. However, Gen Z is closer to this phenomenon because their lives must be connected to the existence of social media as a platform to introduce themselves to the public. Therefore, Gen Z must manage the boundaries between private and public information. This qualitative study uses a descriptive approach, using Sandra Petronio's Communication Privacy Management Theory. The research informants were Gen Z, aged 18-24, who live in Sidoarjo and Surabaya. This study found that Gen Z's oversharing behavior in Instagram Stories can be associated with uploading repetitive or repetitive content. Oversharing activities on Instagram Stories also create conditions where Gen Z is more willing to share the luxury and wealth they possess. Oversharing can also be part of personal branding and labeling for Gen Z. Oversharing not only impacts the person sharing it, but this activity can also have consequences for the audience, such as embarrassment, disturbance, and disappointment. This research shows how Gen Z could overshare on Instagram Stories and how they manage their personal life according to CPM theory.